2020
DOI: 10.1126/sciadv.abd3274
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of circular polarized light in helical 1D perovskite-based photodiode

Abstract: Detection of circularly polarized light (CPL) has a high potential for development of various optical technologies. Conventional photodetectors require optical polarizers on the device to detect polarized light, and this causes substantial losses of sensitivity and resolution in light detection. Here, we report direct CPL detection by a photodiode using a helical one-dimensional (1D) structure of lead halide perovskites composed of naphthylethylamine-based chiral organic cations. The 1D structure with face-sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
237
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(269 citation statements)
references
References 35 publications
7
237
4
Order By: Relevance
“…Notably, the anisotropic g‐factor, which is defined as |g CD− − g CD+ |/2, [18] was calculated to be approximately 0.06 at the LMCT band of [CuCl 4 ] 2− (Figure 1 e), which is one order of magnitude larger than that of the chiral (R‐/S‐MBA) 2 PbI 4 hybrid lead halides (ca. 0.006), [7] and is even larger than the record value of 0.04 recently reported for the chiral one‐dimensional (R‐/S‐NEA)PbI 3 [9a] . Additionally, the CD spectra of (R‐/S‐MBA) 2 CuCl 4 did not change significantly after being stored under ambient conditions for one month, demonstrating the excellent long‐term stability of the as‐prepared films (Supporting Information, Figure S2).…”
Section: Figurecontrasting
confidence: 51%
See 1 more Smart Citation
“…Notably, the anisotropic g‐factor, which is defined as |g CD− − g CD+ |/2, [18] was calculated to be approximately 0.06 at the LMCT band of [CuCl 4 ] 2− (Figure 1 e), which is one order of magnitude larger than that of the chiral (R‐/S‐MBA) 2 PbI 4 hybrid lead halides (ca. 0.006), [7] and is even larger than the record value of 0.04 recently reported for the chiral one‐dimensional (R‐/S‐NEA)PbI 3 [9a] . Additionally, the CD spectra of (R‐/S‐MBA) 2 CuCl 4 did not change significantly after being stored under ambient conditions for one month, demonstrating the excellent long‐term stability of the as‐prepared films (Supporting Information, Figure S2).…”
Section: Figurecontrasting
confidence: 51%
“…For example, Li and co‐authors developed 2D (R‐/S‐MBA) 2 PbI 4 and investigated their CPL and circularly polarized light detection [8b] . Very recently, using one‐dimensional (R‐/S‐NEA)PbI 3 (NEA=1‐(1‐naphtyl)ethylamine) with a highly anisotropic factor of 0.04, Ishii and Miyasaka fabricated a circularly polarized light detector, which achieved a polarization discrimination ratio as high as approximately 25.4 [9a] . Sargent and co‐workers demonstrated a 3 % spin‐polarized photoluminescence of reduced‐dimensional chiral perovskites even in the absence of an applied external magnetic field [10a] .…”
Section: Figurementioning
confidence: 99%
“…The as‐prepared films exhibit strong mirrored CD signals with a giant anisotropic g‐factor of approximately 0.06, which is even greater than the record value (ca. 0.04) recently reported for chiral (R‐/S‐NEA)PbI 3 [9a] . We discuss the origin of giant optical activity in these samples through theoretical modeling based on density functional theory (DFT).…”
Section: Figurementioning
confidence: 88%
“…[19][20][21] More recently, a lowdimensional chiral HOIP has been reported that allows for high CP selectivity in the UV (|gph| = 1.9). [22] Such perovskite devices face challenges relative to competitive technologies however, such as toxicity and instability. While a handful of chiral OPDs have been reported, they demonstrate modest values of |gph| (≤0.1), and other crucial figures of merit (e.g.…”
Section: Introductionmentioning
confidence: 99%